اتحاد بین المسلمین کے تناظر میں صحابہ کرام کےاجتہادی اختلافات سےعصرِ حاضر میں استفادہ - Hussain, Muhammad; Amin, Dr. Muhammad (Al-Irfan, 2022)
In this world full of differences, the existence of scientific differences is a natural thing. It should not be a cause of contention .Differences of understanding in the same event can lead to two different opinions, rather it has happened. In the life of Holy prophet whenever there was a problem, they would turn to the Holy Prophet. and sometimes in his absence would also present the ijtihad and jurisprudential opinions about the Prophet (peace and blessings of Allah be upon him) orders . If there was a mistake in their ijtihaad Holy prophet would correct it. Sometimes it would happen that the Holy Prophet (peace and blessings of Allah be upon him) would justify two completely different opinions in a matter. As is the famous incident of performing Asar prayer on the return from the battle of Ahzab. The Prophet (peace and blessings of Allah be upon him) told the Sahaba to reach Banu Qurayzah and offer Asar prayer. When it was time for Asar prayer on the way, some of the Companions prayed on the way, fearing that the prayer would be missed. We will not offer prayer because we have been commanded to offer prayer in Banu Qurayzah. The Holy Prophet declared both views to be correct. It was learned that even among the Companions, differences arose on the basis of understanding. And in the event of a disagreement, it is not necessary that only one party be right. On the contrary differences of jurisprudence create ways out of difficulties and difficulties, and religion is the name of ease. Therefore, the ease lies in this, but also the modern requirement is to accept the hard work and ijtihad of the mujtahideen with an open heart. And not only should their opinions and ideas be imposed on others by force, but they should be given the freedom to act according to any jurisprudence as they wish. Because all schools of thought are part of Islam and not anything else. Disagreements are beneficial if they do not cause unrest. Because it opens up new avenues of progress and knowledge.